Study on Periplaneta americana (Blattodea: Blattidae) Fungal Infections in Hospital Sewer System, Esfahan City, Iran, 2017 - Khodabandeh, Maryam (J Pathog, 2020)
BACKGROUND: American cockroaches contaminated with pathogens inside hospital manholes can be one of the major problems that health care systems face. OBJECTIVES: The aim of this study was to investigate the fungal infections of American cockroaches in the Esfahan hospital sewage network. The principle goal of the study was about the roaches as a vector of fungi and other pathogens. METHOD: The type of study was descriptive-analytical. A total of 55 American cockroach specimens from the manhole walls of the sewerage system of 7 large hospitals were captured. Samples were taken from the surface of the body, digestive tract, and haemocoel of cockroaches. The specimens were then cultured on Sabouraud dextrose agar separately, and fungi were identified according to the macroscopic and microscopic characteristics. RESULTS: All cockroaches collected from hospitals were infected with fungi. Among the 24 (13 infected and 11 noninfected) (44%) female cockroaches and 31 (18 infected and 13 noninfected) (56%) male cockroaches, it was identified that 40.00% was infected with Aspergillus niger, 3.64% with Rhizopus, 7.27% with Penicillium, and 5.45% with Mucor. 6 cockroaches had no yeast contamination. 17 (30.91%) cockroaches were contaminated with Candida glabrata, 23 (41.82%) cockroaches were contaminated with Candida krusei, and 22 (40%) cockroaches were contaminated with other yeast species. The results of this study showed that Candida krusei had the highest prevalence among the isolated fungi with 35.37% of the digestive system and Aspergillus niger with 70.97% of the surface of the cockroach body. CONCLUSION: The results emphasized the role played by cockroaches as potential pathogenic vectors in hospital environments. Therefore, suitable management is needed for controlling this insect to prevent disease transmission in hospitals.